EP277 Special considerations in quality of life of locally advanced cervical cancer patients. (1st November 2019) - da Silva Dias, D; Gosalbez, B; Alves, L; Luz, P; Madureira, T; Vieira, G; Furtado, I
Abstract : Introduction/Background: Cervical cancer (CC) represents 6% of gynecological malignant tumors. The incidence is decreasing in Portugal, especially with the introduction of nationwide screening program in 2008 and Human Papillomavirus vaccination in 2010. Still, special concern should be placed in improving their quality of life (QoL). Methodology: Retrospective analysis of 109 patients diagnosed with locally advanced cervical cancer in our center between 2010 and 2017. The goal is assessing complications that interfere with the patient's lifestyle such as venous thromboembolism (VTE), ureter hydronephrosis (UHNF), psychological distress (PD) or Palliative care (PC) referral. Results: 109 patients, with median age 56 years old. Mostly admitted through the emergency department (79%), being the most common symptom metrorrhagia (46, 8%). 65, 1% were Stage IIB. Concurrent chemoradiotherapy was applied to 79, 8% (n=87). VTE was highly prevalent, present in 12, 8% of patients (n=14) and an association with OS (p=0, 014) and tumor staging (p=0, 001) was evident. PD including anxiety, depression or uncoping was observed in 25, 7% (n=28), especially in younger women (p=0, 46; HR 0, 96 [95% CI: 0, 93–0, 99]. Psycho-oncology support was provided to 82% (n=23) of patients. UHNF was present in 21, 1% (n=23). Nephrostomy or ureteral stent was performed before the beginning of treatment in 13, 8% (n=15). No difference was observed in OS or DFS in this subgroup. PC was presented to 22% (n=24) patients, although 67% of them were only referred to PC in the last month of life. Conclusion: CC patients have higher incidence of VTE with negative impact in morbimortality and QoL. More studies are necessary to determine the use of prophylactic anticoagulation, especially in patients with concomitant comorbidities. PD may be underdiagnosed and underrepresented in this study. Raised awareness and psycho-oncology support should be provided. PC support should be involved in the patient and families' lives sooner. Disclosure: Nothing to disclose.